Abdominal migraine. (September 2016) - Napthali, Kate; Koloski, Natasha; Talley, Nicholas J
Background: Abdominal migraine (AM) is a syndrome usually recognised in childhood. The syndrome is characterised by episodic attacks of severe abdominal pain and vasomotor symptoms, nausea and vomiting. It is a poorly understood disorder largely due to a limited recognition of this condition by the medical community. However, the publication of AM diagnostic guidelines by the International Headache Society a decade ago and the recognition of AM in the Rome Classification of functional gastrointestinal disorders have helped to legitimise this disorder and facilitate research. Overview: AM is relatively common, affecting up to 4% of the paediatric population. Whilst AM is not believed to continue into adulthood for the majority of children, it has the propensity to develop into probable migraine and recurrent abdominal pain in adulthood. The pathophysiology of this condition remains unclear and as a result treatment for this condition is suboptimal with avoidance of triggers and prophylactic treatment currently recommended when an episode begins. Conclusion: The recognition of AM by the IHS and the Rome Foundation should help facilitate future research into the pathophysiology of this debilitating condition and as a result better treatments for AM should emerge. Randomised controlled trials should be a priority.